Abstraction and illumination: the sublime and Kabbalistic creation motifs in the artworks of Barnett Newman and Mark Rothko - Brown, Rosslyn (2020)
This study will examine the artworks of Barnett Newman and Mark Rothko in relation to the aesthetics of the sublime and the Zoharic Creation account. It will draw most heavily from Pseudo-Longinus’ Peri Hypsous, paying particular attention to its elevation of the early verses of Genesis. References will also be made to the Burkean and Hegelian conceptions of sublimity